Standardized magnetic resonance imaging reporting using the prostate cancer radiological estimation of change in sequential evaluation criteria and magnetic resonance imaging/transrectal ultrasound fusion with transperineal saturation biopsy to select men on active surveillance - Dieffenbacher, Svenja; Nyarangi-Dix, Joanne; Giganti, Francesco; Bonekamp, David; Kesch, Claudia; Wolf, Maya Barbara; Schütz, Viktoria; Gasch, Claudia; Hatiboglu, Gencay; Hauffe, Marcus; Stenzinger, Albrecht; Duensing, Stefan; et al. (European urology focus, 2019)
Background - Contemporary selection criteria for men with prostate cancer (PC) suitable for active surveillance (AS) are unsatisfactory, leading to high disqualification rates based on tumor misclassification. Conventional biopsy protocols are based on standard 12-core transrectal ultrasound (TRUS) biopsy. - Objective - To assess the value of magnetic resonance imaging (MRI)/TRUS fusion biopsy over 4-yr follow-up in men on AS for low-risk PC. - Design, setting, and participants - Between 2010 and 2018, a total of 273 men were included. Of them, 157 men with initial 12-core TRUS biopsy and 116 with initial MRI/TRUS fusion biopsy were followed by systematic and targeted transperineal MRI/TRUS fusion biopsies based on Prostate Cancer Research International Active Surveillance criteria. MRI from follow-up MRI/TRUS fusion biopsy was assessed using the Prostate Cancer Radiological Estimation of Change in Sequential Evaluation (PRECISE) scoring system. - Outcome measurements and statistical analysis - AS-disqualification rates for patients on AS initially diagnosed by either 12-core TRUS biopsy or by MRI/TRUS fusion biopsy were compared using Kaplan-Meier estimates, log-rank tests, and regression analyses. We also analyzed the influence of negative primary MRI and PRECISE scoring to predict AS disqualification using Kaplan-Meier estimates, log-rank tests, and receiver operating characteristic (ROC) curve analysis. - Results and limitations - Of men diagnosed by 12-core TRUS biopsy, 59% were disqualified from AS based on the results of subsequent MRI/TRUS fusion biopsy. In the initial MRI fusion biopsy cohort, upgrading occurred significantly less frequently (19%, p<0.001). ROC curve analyses demonstrated good discrimination for the PRECISE score with an area under the curve of 0.83. No men with a PRECISE score of 1 or 2 (demonstrating absence or downgrading of lesions in follow-up MRI) were disqualified from AS. In our cohort, a negative baseline MRI scan was not a predictor of nondisqualification from AS. Limitations include transperineal approach and extended systematic biopsies used with MRI/TRUS fusion biopsy, which may not be representative of other centers. - Conclusions - MRI/TRUS fusion biopsies allow a reliable risk classification for patients who are candidates for AS. The application of the PRECISE scoring system demonstrated good discrimination. - Patient summary - In this study, we investigated the value of multiparametric magnetic resonance imaging (MRI) and MRI/transrectal ultrasound (TRUS) fusion biopsies for the assessment of active surveillance (AS) reliability using the Prostate Cancer Radiological Estimation of Change in Sequential Evaluation criteria. Standard TRUS biopsies lead to significant underestimation of prostate cancer. In contrast, MRI/TRUS fusion biopsies allowed for a more reliable risk classification. For appropriate inclusion into AS, men should receive either an initial or a confirmatory MRI/TRUS fusion biopsy.
In press
Gesehen am 28.04.2020